PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATIC EDUCATION (RME) DI SD NEGERI NEGERI 086 DALAN LIDANG - Siti Rohani; Kasman; Novebri (EDU RESEARCH, 2024)
This research was carried out with the aim of: 1) finding out how the Realistic Mathematic Education (RME) learning model is implemented in class V mathematics subjects at SD Negeri 086 Dalan Lidang. 2) find out whether the application of the Realistic Mathematic Education (RME) learning model can improve mathematics learning outcomes for students in class V of SD Negeri 086 Dalan Lidang. This type of research is classroom action research (PTK). The subjects were 36 class V students at SD Negeri 086 Dalan Lidang. The classroom action research (PTK) design uses the Kemmis and Taggart model which consists of 2 cycles which include planning, action, observation and reflection. Data collection techniques use tests, documentation and observation. Data analysis used descriptive analysis. The results of the research show that: 1) The implementation of learning in Mathematics learning by applying the Realistic Mathematic Education (RME) learning model went well in accordance with the plans that had been prepared by referring to the steps of the Realistic Mathematic Education (RME) learning model. 2) Student learning outcomes in cycle I were in the good category with a completion percentage of 47.22% with an average of 64.027 and increased in cycle II to a very good category, namely a completion percentage of 80.55% with an average of 80.41. So it can be said that student learning outcomes can be improved through the application of the Realistic Mathematic Education (RME) learning model. By implementing the Realistic Mathematic Education learning model, it can help students solve problems faced in mathematics subjects so that each student's learning outcomes can improve.